DRIVEN PILES FOUNDATION AND SLOPE DESIGN OF AL JABBAR GREAT MOSQUE - Gerald Yohansen, Abel
The design of The Great Mosque "Al-Jabar" GedebageSub-district, Bandung City consists of a mosque structure and an artificial pond around the structure. This final assignment has a purpose to plan foundation systems that can carry the burden from upper-structure and a stable ground slope. The analyses that have to be done are site class, single pile bearing capacity, pile group bearing capacity, the settlement of foundation, determination of driven pile types, and the slope stability design. Standards used in the planning of the project is SNI 8460:2017, SNI 2847:2019, and SNI 1726:2019. In the planning of the project, single pile axial bearing capacity is calculated manually, while single pile lateral bearing capacity is evaluated by a professional application named Ensoft LPILE. In the analyses of shear force, moment, and the deflection that occurs on pile group, Ensoft GROUP application is used, which will be evaluated with the capacity based on Ensoft LPILE and the used brochure. The settlement that occurs on the foundation, caused by the burden of upper-structure will be analyzed by a program named MIDAS GTS NX and will be evaluated based on provisions on SNI 8460:2017. The slope used for the artificial pond will be analyzed by MIDAS GTS NX and will be evaluated based on SNI 8460:2017. All of the analyses that has been done is suitable according to the standard boundaries from all of the SNI above.